Makna Simbolik pada Tradisi Cheng Beng di Kompleks Perkuburan Sentosa Kota Pangkalpinang - Annisa, Syafa Kamila Nur; Purnama, Dadang Hikmah; Reftantia, Ghina; Oktanedi, Aldri (Jurnal Empirika, 2025)
This study aims to uncover the symbolic meanings embedded in the Cheng Beng tradition practiced by the Chinese community at the Sentosa Cemetery Complex, Pangkalpinang City. Cheng Beng is an annual ritual involving various activities such as cleaning graves, offering food and drinks, praying, and burning symbolic paper. Using a descriptive qualitative approach, this study employed in-depth interviews, observations, and documentation as data collection methods. Symbols such as incense, candles, five-color paper, spirit money, and food offerings carry profound meanings. Cleaning graves symbolizes respect for ancestors, candles represent spiritual enlightenment, and collective prayers signify gratitude, family solidarity, and hopes for ancestral protection. Beyond honoring ancestors, the tradition strengthens family bonds, preserves Chinese cultural values, and educates younger generations about the importance of filial piety. By employing the symbolic interactionism perspective, this research finds that symbolic meanings are constructed through social and cultural interactions within the Chinese community. The findings affirm that Cheng Beng is a spiritual ritual and a medium for preserving cultural identity, fostering family relationships, and maintaining community solidarity amidst modernization challenges. This tradition reflects the Chinese community's enduring values of respect, unity, and cultural heritage.